2014
DOI: 10.1021/am502605s
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Storage Properties of Pristine and (Mg, Cu) Codoped ZnFe2O4 Nanoparticles

Abstract: ZnFe2O4 and MgxCu0.2Zn0.82-xFe1.98O4 (where x = 0.20, 0.25, 0.30, 0.35, and 0.40) nanoparticles were synthesized by sol-gel assisted combustion method. X-ray diffraction (XRD), FTIR spectroscopy, Raman spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and Brunauer-Emmett-Teller (BET) surface area studies were used to characterize the synthesized compounds. ZnFe2O4 and the doped compounds crystallize in Fd3m space group. The lattice parameter of ZnFe2O4 is calculated to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…[16][17][18]. Among them, sonochemical synthesis method is advantageous for the synthesis of nanoparticles due to simple, good control of size, highly monodispersed nanoparticles, and very small nanoparticles, etc.…”
mentioning
confidence: 99%
“…[16][17][18]. Among them, sonochemical synthesis method is advantageous for the synthesis of nanoparticles due to simple, good control of size, highly monodispersed nanoparticles, and very small nanoparticles, etc.…”
mentioning
confidence: 99%
“…The band at ∼650 cm −1 for ZnFe 2 O 4 corresponds to motion of oxygen in the ZnO 4 tetrahedral. Previous papers also offer the same explanation [48][49][50][51][52][53]. Upon with Ni + substitution the high frequency band ranges from ~630 to ~670 due to the change in the environment of the tetrahedral.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 61%
“…Normal spinel structure ZnFe 2 O 4 permits five active Raman modes (A 1g + E g +3T 2g ) [48,49]. Usually, wave numbers above 600 cm -1 mostly corresponds to the motion of oxygen in tetrahedral AO 4 groups that are of the A 1g type, while the low frequency phonon modes are related to metal ion involved in octahedral sites (BO 6 ) [50,51].…”
Section: Structural and Morphological Characterizationmentioning
confidence: 99%
“…22 It is desirable to be made to replace Co in Co 3 O 4 by other cheaper and alternative elements which are friendly to environment like MCo 2 O 4 (M ¼ Zn, Cu, Ni, Mg, Fe and Mn) 11,18,20,[22][23][24][25][26] generally having higher reversible capacity 27 by concluded that metals with inverse spinel structure can be incorporated with more Li ions, compared to mixed and normal spinel. 15,28 Various chemical and physical methods have been adopted for the preparation of these metal oxides. [47][48][49][50][51][52][53][54] and some Li + diffusion problems which will cause worse electrochemical preference such as voltage hysteresis and spinel broken spinel lattice.…”
Section: Introductionmentioning
confidence: 99%